Comparison Of Network Attacks Before and During Covid-19 On Educational Institutions - Grzegorz PODGORSKI (Communications of International Proceedings, 2021)
The aim of the article will be to present the results of research on network attacks on a university unit in the period before and during the corona virus pandemic in Poland. The purpose of the research is to verify whether the global situation has contributed to a change in the types and directions of network attacks against educational institutions in Poland, based on the example of a selected unit. The article is divided into two parts. The first is theoretical. The second is the analysis of network attack data collected from an educational organization over two periods of time: before and during Covid-19. The types of attacks and their vector will be analyzed. The study presents the actual data that was registered in the organization. Conclusions have also been drawn regarding the relationship of network attacks in the context of the coronavirus pandemic and the transition to the remote working model. The aim was to investigate whether the period of the pandemic changes the realities of IT security threats in universities? Answers to these questions, as well as data analysis, will allow to obtain measurable benefits in the context of information security. These benefits will translate into an increase in the level of information security. Firstly, by identifying the elements of the infrastructure, which at the present time is particularly vulnerable and becomes the target of network attacks. Secondly, by revising and introducing appropriate amendments to the existing security mechanisms in the context of the most attacked elements of the ICT infrastructure.
Keywords: Case Study; Network Attacks; Information Security.